Sphaerolaimus uncinatus nov. spec. (Nematoda, Monhysterida) aus der Tiefsee - Freudenhammer, I. (Veröff. Inst. Meersesforsch. Bremerh., 1970)
Locality: Iberian Deep-Sea; Cabinet:n131
NeMys doc_id: 7786 NeMys doc_id: 4807